Quantum-Fluid Interpretation of Enzymatic Tunnels and Energy Transport - Barack Ndenga (Publisher, 2025)
Enzymatic tunnels—internal channels guiding substrates, protons, electrons, or conformational energy—are traditionally described using classical diffusion, transition state theory, or vibrational coupling. Here, I propose a novel framework: the Quantum-Fluid Interpretation, where enzymatic tunnels behave as coherent nano-fluids governed by π-field dynamics, enabling long-range energy transport, ultrafast communication, and directionality without significant energy loss. This model integrates quantum hydrodynamics, π-coherence fields, and nonlinear curvature-driven flows to describe tunneling, proton transfers, allosteric propagation, and catalytic acceleration. To my knowledge, this is the first article to formalize enzymatic tunnels as quantum fluid conduits, establishing a new branch of bio-quantum dynamics.
This work introduces a novel theoretical framework in which enzymatic tunnels are reinterpreted as quantum-fluid coherence channels rather than simple geometric pathways. Guided by π-field hydrodynamics, these tunnels support coherent, directed energy transport at the nanoscale, providing a unified explanation for ultrafast proton movement, long-range communication between protein sites, low-dissipation energy flow, and the remarkable sensitivity of catalytic efficiency to single-point mutations. In this article, I develop a quantum-hydrodynamic model incorporating coherence density, phase-field dynamics, and the π-induced quantum potential 𝑄𝜋. The resulting framework predicts: ballistic-like transport within enzymatic tunnels, π-gradient–driven directionality, coherence-supported reduction of effective energy barriers, mutation-induced π-defects disrupting transport, and the emergence of nanoscale quantum-fluid vortices. To the best of my knowledge, this is the first scientific work to formally characterize enzymatic tunnels as quantum-fluid conduits governed by π-field dynamics. This establishes a new research direction at the intersection of quantum biology, enzymology, and nanophysical modeling, which I refer to as Quantum Fluid Enzymology (QFE). The deposition includes conceptual figures, theoretical equations, and a computational π-fluid simulation approach for tunnel transport